Utilization of Open Space in Medan City During the Covid-19 Pandemic - Eddy Syahrial; Destanul Aulia (Randwick International of Social Science Journal, 2022)
This study aims to analyze the use of open space in the city of Medan during the Covid-19 pandemic can be seen from the perception, needs, quality and utilization. This type of research is an analytical survey with cross sectional design. Total sample of 200 respondents obtained by purposive sampling. This research instrument uses a questionnaire. The Data obtained in this study were analyzed by conjoint analysis. The results of the conjoint analysis show that the perception attribute is needed for officers to oversee the implementation of the covid-19 protocol in the field, the needs attribute, the field is needed to reduce noise during the covid-19 pandemic, the field is needed for sunbathing, and the field is needed to play with family during the covid-19 pandemic. Quality attributes, the availability of jogging tracks for running and walking, the availability of trees and plants around the field are of sufficient quality in the field during the covid-19 pandemic. The availability of play facilities, the availability of facilities for recreation and the availability of means to improve the family economy. And the attributes of utilization according to field respondents were used every morning, during the covid-19 pandemic, the field was used every holiday, and the field was more widely used during the covid-19 pandemic. The Medan City Government is expected to form officers to oversee the implementation of the covid-19 protocol in Medan City Field